Rare earth doped synthetic opals and inverse opals - Bueno, L. A.; Bertholdo, R.; Barros, D. A.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Spie - Int Soc Optical Engineering, 2002)
Monodisperse spheres of silica and latex were obtained by a surfactant free styrene polimerization and the Stober method respectively. Controlling settling either by centrifugation or by dip-coating colloidal crystals could be obtained. Silica inverse opals were prepared by using the latex colloidal crystals as templates and TEOS/ethanol solution. Eu3+ containing silica spheres were obtained dispersing silica spheres in Eu(NO3)(3) isopropanol solutions. Emission spectra suggest the formation of an amorphous Eu3+ containing phase well adhered at the spheres surface. The utilization of solutions of trifluoroacetates salts of Pb2+ and Eu3+ was observed to destroy the silica spherical pattern when samples are treated at 1000degreesC. In that case nanocrystals of PbF2 and amorphous silica were obtained after heat treatment.
Keywords: opals; inverse opals; lanthanide ions